STIMULATING DEVELOPMENT OF CHILDREN AGES 4-5 YEARS - Sumiyati Sumiyati; Suparmi Suparmi; Aris Santjaka; Wanodya Hapsari (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
Development of moral and the child's personality is formed in childhood so that any small irregularities if not detected and treated properly, will reduce the quality of human resources. Stimulation, especially in the family such as the provision of play equipment, socialization of children, involvement of mothers and other family members of the children's activities will enhance child development. Applying the results of research conducted by Prodi DIII Midwifery Purwokerto on Childhood Development Stimulation 4-5 Years In the village of the District Karangtengah Baturraden. Expected mothers Karangtengah village District of Baturraden can improve knowledge about Childhood Development Stimulation 4-5years and apply in their lives. An understanding of the stimulation of the mothers delivered through health education with lectures, demonstrations, discussions and through video on stimulation of development of children aged 4-5 years. Mothers / caregivers before given lectures and discussions on stimulation of development of children aged 4-5 years, first performed pre-test of stimulation progress made by the mothers / caregivers to the toddler. Health education is expected to increase the knowledge and understanding of mothers about the importance of appropriate stimulation to the child development stages 4-5 years on aspects of gross motor, fine motor, speech-language and sosislisasi-independence according to Pre Screening Questionnaire Development (KPSP).